Safe distances between groundwater-based water wells and pit latrines at different hydrogeological conditions in the Ganges Atrai floodplains of Bangladesh. Issue 1 (December 2016) - Islam, M.; Mahmud, Zahid; Islam, M.; Saha, Ganesh; Zahid, Anwar; Ali, AHM; Hassan, M.; Islam, Khairul; Jahan, Hasin; Hossain, Yakub; Hasan, M.; Cairncross, Sandy; et al.
Abstract Background Groundwater drawn from shallow tubewells in Bangladesh is often polluted by nearby pit latrines, which are commonly used toilets in rural and sub-urban areas of the country. Methods To determine the minimum safe distance of a tubewell from a pit latrine in different hydrogeological conditions of Bangladesh, 20 monitoring wells were installed at three study sites (Manda, Mohanpur and Bagmara) with the vertical and horizontal distances ranging from 18–47 to 2–15 m, respectively. Water samples were collected three times in three seasons and tested for faecal coliforms (FC) and faecal streptococci (FS) as indicators of contamination. Soil samples were analysed for texture, bulk density and hydraulic conductivity following standard procedures. Sediment samples were collected to prepare lithological logs. Results When the shallow aquifers at one of the three sites (Mohanpur) were overlained by 18–23-m-thick aquitards, the groundwater of the monitoring wells was found contaminated with a lateral and vertical distances of 2 and 31 m, respectively. However, where the aquitard was only 9 m thick, contamination was found up to lateral and vertical distances of 4.5 and 40.5 m, respectively. The soil textures of all the sites were mainly composed of loam and sandy loam. The hydraulic conductivities in the first aquifer at Manda, Mohanpur and Bagmara were 5.2–7.3, 8.2 and 1.4–15.7 m/h, respectively. Conclusions The results showed that the safe distance from the tubewell to the pit latrine varied from site to site depending on the horizontal and vertical distances of the tubewell as well as hydrogeological conditions of a particular area.